2017
DOI: 10.1002/adma.201603997
|View full text |Cite
|
Sign up to set email alerts
|

Nanopolymersomes with an Ultrahigh Iodine Content for High‐Performance X‐Ray Computed Tomography Imaging In Vivo

Abstract: Biocompatible and biodegradable nanopolymersomes with an unprecedented iodine content, low viscosity, and iso-osmolality achieve significantly enhanced CT imaging of blood pool and the reticuloendothelial system. Moreover, in subcutaneous and orthotopic tumor models in mice, they show enhanced in vivo imaging when compared to iohexol, a clinically used small-molecule contrast agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…Recently, Zou et al designed biocompatible and biodegradable iodinated nanopolymersomes with high stability and low viscosity via self‐assembly of poly(ethylene glycol)‐ b ‐poly(iodine trimethylene carbonate) (PEG‐ b ‐PIC) diblock copolymer ( Figure a) . These iodine‐rich nanopolymersomes (IPs) exhibited an ultrahigh iodine content (60.4 wt.%) and 1.2‐fold higher CT contrast efficacy than Iobitridol (Figure b).…”
Section: X‐ray‐excited Structural/functional Imagingmentioning
confidence: 99%
“…Recently, Zou et al designed biocompatible and biodegradable iodinated nanopolymersomes with high stability and low viscosity via self‐assembly of poly(ethylene glycol)‐ b ‐poly(iodine trimethylene carbonate) (PEG‐ b ‐PIC) diblock copolymer ( Figure a) . These iodine‐rich nanopolymersomes (IPs) exhibited an ultrahigh iodine content (60.4 wt.%) and 1.2‐fold higher CT contrast efficacy than Iobitridol (Figure b).…”
Section: X‐ray‐excited Structural/functional Imagingmentioning
confidence: 99%
“…An in vivo contrast agent would make investigations with reduced sample size possible and allow for the study of vascular changes within the same animal over time; however, development of an in vivo contrast agent is not within the scope of this study. Currently, there exist in vivo contrast agents that reside within the blood pool for extended periods of time [ 43 , 44 ]; thus, we expect that the incorporation of Er into an in vivo agent is possible.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that mice injection reached significant enhancement in liver, lymph nodes, and spleen 30 min after injection. Biodegradable nanopolymers with ultrahigh iodine content with high biocompatibility reported by Zou et al (). The group managed to produce polymeric nanoparticles, using iodine‐functionalized trimethylene carbonate monomer, in 100 nm mean diameter having 60.4% wt iodine content with low viscosity.…”
Section: Nanoparticle‐based Staining Agentsmentioning
confidence: 97%
“…(a) Sagittal and coronal sections and (b) dynamic contrast enhanced density (ΔHU) of aorta of C57BL/6 mice after IV injection of IPs (500 mg I kg −1 ). (c) in vivo CT images and (d) dynamic contrast enhanced density (ΔHU) of several major organs at C57BL/6 mice after IV injection of IPs at different time intervals (Zou et al, ) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Nanoparticle‐based Staining Agentsmentioning
confidence: 99%